Independent domains for recruitment of PRC1 and PRC2 by human XIST - Dixon-McDougall, Thomas (PLoS Genet, 2021)
XIST establishes inactivation across its chromosome of origin, even when expressed from autosomal transgenes. To identify the regions of human XIST essential for recruiting heterochromatic marks we generated a series of overlapping deletions in an autosomal inducible XIST transgene present in 8p of the HT1080 male fibrosarcoma cell line. We examined the ability of each construct to enrich its unified XIST territory with the histone marks established by PRC1 and PRC2 as well as the heterochromatin factors MacroH2A and SMCHD1. Chromatin enrichment of ubH2A by PRC1 required four distinct regions of XIST, and these were completely distinct from the two domains crucial for enrichment of H3K27me3 by PRC2. Both the domains required, as well as the impact of PRC1 and PRC2 inhibitors, suggest that PRC1 is required for SMCHD1 while PRC2 function is necessary for MacroH2A recruitment, although incomplete overlap of regions implicates roles for additional factors. This cooperativity between factors contributes to the requirement for multiple separate domains being required for each feature examined. The independence of the PRC1/PRC2 pathways was observed when XIST was expressed both autosomally or from the X chromosome suggesting that these observations are not purely a result of the context in which XIST operates. Although independent domains were required for the PRC1 and PRC2 pathways overall all regions tested were important for some aspect of XIST functionality, demonstrating both modularity and cooperativity across the XIST lncRNA.